Straw Throwing Method and Tractors Forward Speed Impacts on the Straw Picking Up and Chopping Machine's Performance - Affan Othman Hussein (Zanco Journal of Pure and Applied Sciences, 2020)
Wheat straw is a valuable by-product of grain harvesting in Kurdistan region basically for livestock feeding. It is thrown behind the harvester on the ground in different forms like heaps, windrows or spread in the field. Straw collecting in the field needs a lot of labor; it is also a costly and time-consuming operation. Recently, there has been a new operation in the field of straw chopping machines which picks up the straw from the ground, cuts and blows it to a trolley and all of this in one operation. This study was conducted to find the effect of some operational factors on the machines performance. The results show that collecting the straw as windrows in the field by the straw chopping machine gives better performance than the heaps. A tractor with 72 HP is sufficient for operating the straw picking-up and chopping machine with a trolley behind. Five different forward speeds (S1=3.12, S2=4.22, S3=5.21, S4=6.31 and S5=7.51) km/h were examined for straw picking-up and chopping as windrows to find their effects on the performance of the machine, it was found that with S3 or S4, the machine shows the best performance in terms of fuel and time consumption, throughput capacity, straw recovery, throughput efficiency and acceptable slippage percentage.